Synthesis and antimycobacterial screening of new thiazolyl-oxazole derivatives - Abhale, Yogita K.; Sasane, Amit V.; Chavan, Abhijit P.; Shekh, Saddam Husen; Deshmukh, Keshav K.; Bhansali, Sujit; Nawale, Laxman; Sarkar, Dhiman; Mhaske, Pravin C. (European Journal of Medicinal Chemistry, 2017)
In the present study a series of 4-methyl-2-aryl-5-(2-aryl/benzyl thiazol-4-yl) oxazole (4a-v) have been synthesized and evaluated for their preliminary antitubercular, antimicrobial and cytotoxicity activity. Among all the synthesized compounds, 4v reported comparable activity against dormant M. tuberculosis H37Ra and M. bovis BCG strains with respect to standard drug rifampicin. The active compounds from the antitubercular study were further tested for anti-proliferative activity against HeLa, A549 and PANC-1 cell lines using MU assay and showed no significant cytotoxic activity at the maximum concentration evaluated. Further, the synthesized compounds were found to have potential antibacterial activities with MIC range of 2.1-26.8 mu g/mL. High potency, lower cytotoxicity and promising antimycobacterial activity suggested that these compounds could serve as good leads for further optimisation and development. (C) 2017 Elsevier Masson SAS. All rights reserved.

Synthesis, antimycobacterial screening and molecular docking studies of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthiazole derivatives - Abhale, Yogita K.; Shinde, Abhijit D.; Deshmukh, Keshav K.; Nawale, Laxman U.; Sarkar, Dhiman; Choudhari, Prafulla B.; Kumbhar, Santosh S.; Mhaske, Pravin C. (Medicinal Chemistry Research, 2017)
A series of 4-aryl-4′-methyl-2′-aryl-2,5′-bisthia- zole derivatives (5a–o) were synthesized and screened for inhibitory activity against Mycobacterium tuberculosis H37Ra (ATCC 25177) and Mycobacterium bovis BCG (ATCC 35743) strains. Five lead compounds (5e, 5f, 5g, 5h, and 5o) were further confirmed from their dose dependent effect against MTB and Bovine–Calmette–Guerin. The most promising compounds 5f (MIC90: 11.32 μg/mL), 5h (MIC90: 11.59 μg/mL), and 5o (MIC90: 23.64 μg/mL) showed strong antitubercular activity against dormant MTB and BCG as well as almost insignificant cytotoxicity up to 100μg/mL against HeLa, A549, and PANC-1 human cancer cell lines. Further, the synthesized compounds were found to have potential antibacterial activity against Gram-negative bac- teria, Escherichia coli, Pseudomonas flurescence and Gram- positive bacteria, Staphylococcus aureus, Bacillus subtilis. Most of the synthesized compounds showed moderateactivity against fungal strain Candida albicans. Molecular docking studies of these compounds showed significant interactions with crystal structure of the cytochrome P45014α-sterol demethylase (CYP51) PDB ID: 1E9X. Hydrogen bond interactions with SER261 and VAL395 are important interactions for selective inhibition of designed inhibitors. Compounds 5f, 5h, and 5o showed significant interactions with 1E9X. All the experimental results promote us to consider this series as a starting point for the devel- opment of novel, selective and more potent antitubercular agents in the future.